Negotiating a new chair package: context and considerations. Issue 1 (17th January 2023) - Weidner, Amanda; Elwood, Samantha; Koopman, Richelle; Phillips, Julie; Schmitz, David; Li, Li; Catinella, A Peter; Robinson, Jehni; Rianon, Nahid; Peek, C J; Asif, Irfan
Abstract : Negotiating a resource package as a potential new department chair is common practice in academic medicine. The foundations for this negotiation include the historical presence of the department in relation to the broader institution, projections for future growth, accounting for mission/vision, resource needs (space, personnel, finances, etc), faculty and staff development, and external partnerships within and outside the institution. Despite similarities in this process across departments, many nuances influence the development of a specific new chair package, such as, department size; desires, perspectives and talents of the incoming chair, the department faculty, the medical school and dean; prevailing agendas and mission imperatives; and the overall priorities of the institution. With strategy and forethought, a new chair package can promote a successful chair tenure and departmental growth. Assembled through the Association of Departments of Family Medicine with input from several dozen department chairs and senior leaders, this is intended to serve as a practical guide to new chair packages for chair candidates.